FRI0121 Concordance of 6 composite disease activity measures in a peruvian population with rheumatoid arthritis. (23rd January 2014) - Ugarte-Gil, M.; Garcia-Poma, A.; Gamboa-Cardenas, R.; Mora, C.; Cucho, M.; Terrazas, H.; Pastor, C.; Rhor, E.; Acevedo-Vasquez, E.; Segami, M.I.
Abstract : Background: The management of the Rheumatoid Arthritis using standardized activity measures have probed better outcomes than usual care. There are few studies that evaluated the concordance of the most used activity measures in Hispanic population. Objectives: To evaluate concordance and agreement of the original DAS28/ESR-4 item composite disease activity status measure with 3 of its derivatives: DAS28/CRP-4 item, DAS28/ESR-3 item, DAS28/CRP 3-item, SDAI and CDAI when classifying patient disease activity by European League of Associations for Rheumatology (EULAR) criteria, using an established rheumatoid arthritis (RA) patient cohort. Methods: A cross-sectional study was performed at the Rheumatology Departments of the two biggest hospitals of Lima, Peru (since 2005 to 2009). Disease activity was evaluated using DAS28/ESR-4 item, DAS28/CRP-4 item, DAS28/ESR-3 item, DAS28/CRP 3-item, SDAI and CDAI. We analyzed the degree of agreement using kappa (k) index for these cutoff points: DAS28-ESR 4 or 3 item (<2.6: remission, 2.6 to <3.2: mild activity, 3.2 to 5.1: moderate activity and>5.1: severe activity), DAS28-CRP 4 or 3 item (<1.8: remission, 1.8 to <2.5: mild activity, 2.5 to 4.1: moderate activity and>4.1: severe activity), SDAI (<3.3: remission, 3.3 to <11: mild activity, 11 to 26: moderate activity and>26: severe activity) and CDAI (<2.8: remission, 2.8 to <10: mild activity, 10 to 22: moderate activity and>22: severe activity). Results: We included 615 patients, with an average age of 57.54 years (SD 13.34), and a disease duration of 15.29 years (SD: 11.23); 536 (87.2%) were female. The average DAS28/ESR-4 item was 4.87 (SD 1.44). According to DAS28/ESR-4 item 33 (5.4%) were in remission, 52 (8.5%) showed mild activity, 258 (42.0%) moderate and 272 (44.2%) severe activity. Agreement between the categories using DAS28/ESR-4 item and DAS28/CRP-4 item was 79.3% (k: 0.68); DAS28/ESR-4 item and DAS28/ESR-3 item was 84.4% (k: 0.75), DAS28/ESR-4 item and DAS28/CRP-3 item was 68.8% (k: 0.53), DAS28/ESR-4 item and SDAI was 65.1% (k: 0.47), DAS28/ESR-4 item and CDAI was 69.2% (k: 0.54). Conclusions: The DAS28/ESR-4 item, and its variants, SDAI, and CDAI are valid tools for disease activity assessment in Peruvian population with RA, and present a moderate or good agreement between its categories. References: Gamboa RV, Ugarte-Gil MF, Diaz K, Alfaro JL, Cucho M, et al. New cut off points of the DAS28(CRP) to define categories of disease activity in Peruvian patients with rheumatoid arthritis. Ann Rheum Dis 2011; 70 (Suppl3): 592 Disclosure of Interest: None Declared